Advanced machine learning application for odor and corrosion control at a water resource recovery facility. (25th August 2021) - Yang, Fenghua; Pluth, Thaís Bremm; Fang, Xing; Francq, Kyle Bradley; Jurjovec, Matthew; Tang, Yongning
Abstract: The objective of this study was to develop a machine learning (ML) application to determine the optimal dosage of sodium hypochlorite (NaOCl) to curtail corrosion and odor by H2 S in the headworks of a water resource recovery facility (WRRF) without overly consuming volatile fatty acids (VFAs) that are essential for the enhanced biological phosphorus removal. Given the highly diverse datasets available, three subproblems were formulated, and three cascaded ML modules were developed accordingly. The final ML models, chosen based on performance, were able to predict various targeted variables. More specifically, in Module 1, a recurrent neural network (RNN) was designed to predict wastewater characteristics. In Module 2, a random forest (RF) classifier and a support vector machine (SVM) classifier were built with the information from Module 1 along with other datasets to predict the concentrations of VFAs and H2 S, respectively. Finally, in Module 3, with the information obtained from Module 2, another RF classifier was developed to predict NaOCl dosage to reduce H2 S but keeping VFAs within the target range. These efforts are relevant and informative for WRRFs that are considering developing Intelligent Water Systems to predict the wastewater characteristics to make operational improvements. Practitioner Points: A recurrent neural network (RNN) using long short‐term memory (LSTM) successfully predicted influent wastewater parameters. A support vector machine classifier predicted hydrogen sulfide (H2 S) with 97.6% accuracy. The concentration of VFAs, an important parameter in EBPR, was predicted using a random forest classifier with 93.4% accuracy. The optimal NaOCl dosage for H2 S control can be predicted with a random forest classifier using H2 S, VFAs, and flow. Abstract : Determining the proper amount of sodium hypochlorite (NaOCl) to dose for odor and control without impact downstream treatment is always challenging for wastewater treatment facilities. This project developed three cascade machine learning (ML) modules using plant influent characteristic and other online operational data to forecast hydrogen sulfide and volatile fatty acids levels. Those information, together with the target levels are further used in the ML model to predict the optimum amount of NaOCl that should be applied for headwork odor/corrosion without negatively impacting the downstream enhanced biological phosphorus removal performance.